Ruxolitinib and oHSV combination therapy increases CD4 T cell activity and germinal center B cell populations in murine sarcoma - Ravi Dhital; Yeaseul Kim; Doyeon Kim; Ilse Hernandez-Aguirre; Jack Hedberg; Alexia Martin; Kevin A. Cassady (Molecular Therapy: Oncology)
Malignant peripheral nerve sheath tumors (MPNSTs) are a highly aggressive neoplasm of the peripheral nervous system and are resistant to most conventional cancer therapies. We previously showed that pretreatment with ruxolitinib (RUX) enhanced the efficacy of oncolytic herpes simplex virus (oHSV) virotherapy in this murine sarcoma model. A low abundance of tumor-infiltrating leukocytes and limitations in conventional flow cytometry restrict analyses to a narrow subset of immune cells, potentially introducing a confirmation bias. To address these limitations, we developed a 46-color spectral flow cytometry panel for the detailed analysis of immune cell dynamics following repeated oHSV dosing. Beyond the cytotoxic T lymphocyte (CTL) and regulatory T cell (Treg) changes reported in our earlier studies, RUX+oHSV treatment modulates myeloid and other lymphoid compartments, including germinal center B cell populations with enhanced activation. RUX+oHSV therapy also increased cytokine-expressing CD4(+) populations, predominantly granzyme B(+) cytotoxic-like, interferon (IFN)-γ(+) T helper type 1 (Th1)-like, and interleukin (IL)-21(+) T follicular helper (Tfh)-like phenotypes, within the tumor infiltrates, suggestive of potential tertiary lymphoid structure development in the treated tumors. Here, we illustrate the utility of a high-dimensional spectral flow cytometry panel that permits simultaneous evaluation of intratumoral CD4/CD8 T cell, Treg, γδ-T cell, natural killer T (NKT) cell, B cell, NK cell, monocyte, macrophage, granulocyte, myeloid-derived suppressor cell (MDSC), and dendritic cell functional changes from RUX+oHSV-treated MPNSTs.